Harmonic Scalpel® haemorroidectomy at rural tertiary care centre: a review of 52 cases - Saxena, Divish; Akhtar, Murtaza; Rode, Avinash; Tandon, Mrinal (International Surgery Journal, 2016)
Background:Haemorrhoids is a common problem in spicy food loving population of India. Multiple modalities are available for management of grade II and grade III hemorrhoids. The main postoperative complications associated with any of these procedures are pain and bleeding per rectum. Harmonic Scalpel® (Ethicon Endosurgery) Haemorrhoidectomy was evaluated in this study for post-operative complications and symptomatic relief. Methods:We analyzed 52 patients of hemorrhoids of grade II, III and IV who underwent harmonic scalpel haemorroidectomy by a classical Milligan-Morgan technique. The outcome factors analyzed were total operative time, blood loss, post-operative pain on visual analogue scale, any other complication and days of hospital stay. Results:Of all the 52 patients, the operative time was less than 10 minutes in 29 patients (55.76%) and the blood loss, as was measured by number of soaked gauze pieces only one gauze piece was soaked in 33 patients (63.46%). The Average Post-operative pain score measured on Visual Analogue Scale (VAS) at 12, 24 & 48 hours were 6.54, 4.52 and 3.12 respectively. In all patients postoperative period and follow up was uneventful except for one patient who developed anal stricture and presented with chronic constipation. A weekly anal dilatation was performed in this patient with anal dilators for 2 months and patient was relieved thereafter. Conclusions:Harmonic Scalpel® hemorrhoidectomy is a safe and fast modality of treatment for 2nd , 3rd & 4th degree of hemorrhoids whether single or multiple, requiring very less operating time, with no major post-operative complications and early return to day to day activities.